Strategi TNI Angkatan Laut Dalam Pengamanan Batas Maritim NKRI: Kajian Historis-Strategis - -, Marsetio - (Citra Lekha, 2013)
The main aim of this article is to trace the role of Indonesian Navy for securing the ocean borders of the Integrated State ofthe Republic of Indonesia during the course of Indonesia history since its independence in 1945. For Indonesia, the issue of ocean borders is very interesting to be discussed consedering the fact that most of part ( 80 percent) the Indonesian territory comprises of ocean waters. It stretches across the tropical waters of the Indian Ocean and the Pacific, from South-eastern Asia to Northern Australia. It is not suprising that Indonesia has a complicated ocean borders with its neighbors. In this respect, the role of Indonesian Navy to secure the ocean borders in the Indonesia history cannot be neglected. For that purpose it is very interesting to understand the strategy of Indonesian Navy in securing the borders. Key Words: Indonesia Navy, strategy, archipelagic state, ocean borde